Higher education via the lens of industry 5.0: Strategy and perspective - Mohamed Ashmel Mohamed Hashim; Issam Tlemsani; Rachel Mason-Jones; Robin Matthews; Vera Ndrecaj (Social Sciences and Humanities Open, 2024)
This study delves into the transformative potential of Industry 5.0 (I5.0) within the realm of higher education, employing a robust empirical model. Significantly, this model incorporates (a) research and development, (b) business innovation, and (c) human centricity, placing a pivotal emphasis on unravelling the conclusive impact of I5.0 on higher education. The overarching objective is to position human elements at the core of the higher education system, thereby not only enhancing operational efficiency and growth but also fostering sustainable development for the greater good of humanity.The primary research objectives are to elevate the focus on the evolutionary literature of I5.0, develop pertinent I5.0 profiles specific to higher education, chart a comprehensive roadmap for the cultivation of I5.0, and construct a fundamental model for the systematic analysis of its emerging impact. I5.0, with its novel strategic opportunities, proves particularly instrumental in enhancing resilience within higher education institutions. This allows for a strategic reorientation towards sustainability, with a heightened commitment to societal and environmental contributions (people, profit, and planet).Employing a grounded theory methodology, this research selectively underscores the evolutionary and systematic impact of I5.0 on higher education by leveraging theoretical concepts, individual experiences, and diverse perspectives. Our findings highlight the nascent awareness of I5.0 within higher education institutions, with relatively scarce new insights. The adoption of novel knowledge is characterized by a lack of systematic approach, necessitating innovative methods and models for effective implementation.This paper articulates a tetra-dimensional empirical model (experimental model) tailored for the integration of I5.0 in higher education, comprising the theoretical dimension, application dimension, technical dimension, and practice dimension. It is essential to acknowledge the limitation of this research, which confines its assessment of I5.0 impact to the higher education sector. Ultimately, the implications of this research extend beyond the theoretical realm, offering practical insights and implementable recommendations for policy development.